Rethinking the Conditions and Mechanism for Glymphatic Clearance - Ferris, Craig F. (Frontiers in Neuroscience, 2021)
Critical studies that form the foundation of the glymphatic system and the clearance of metabolic by-products of unwanted proteins from the brain are reviewed. Concerns are raised about studying glymphatic flow in anesthetized animals and making assumptions about the whole brain based upon data collected from a cranial window on the cortex. A new model is proposed arguing that the flow of cerebral spinal fluid and parenchymal clearance in the perivascular system of unwanted proteins is regulated by circadian changes in brain temperature and blood flow at the level of the microvasculature.